Efficacy and safety of treatment with biologicals (benralizumab, dupilumab and omalizumab) for severe allergic asthma: A systematic review for the EAACI Guidelines ‐ recommendations on the use of biologicals in severe asthma. Issue 5 (18th May 2020) - Agache, Ioana; Rocha, Claudio; Beltran, Jessica; Song, Yang; Posso, Margarita; Solà, Ivan; Alonso‐Coello, Pablo; Akdis, Cezmi; Akdis, Mubeccel; Canonica, Giorgio W.; Casale, Thomas; Chivato, Tomas; et al.
Abstract: Allergic asthma is a frequent asthma phenotype. Both IgE and type 2 cytokines are increased, with some degree of overlap with other phenotypes. Systematic reviews assessed the efficacy and safety of benralizumab, dupilumab and omalizumab (alphabetical order) vs standard of care for patients with uncontrolled severe allergic asthma. PubMed, Embase and Cochrane Library were searched to identify RCTs and health economic evaluations, published in English. Critical and important asthma‐related outcomes were evaluated. The risk of bias and the certainty of the evidence were assessed using GRADE. All three biologicals reduced with high certainty the annualized asthma exacerbation rate: benralizumab incidence rate ratios (IRR) 0.63 (95% CI 0.50 − 0.81); dupilumab IRR 0.58 (95%CI 0.47 − 0.73); and omalizumab IRR 0.56 (95%CI 0.42 − 0.73). Benralizumab and dupilumab improved asthma control with high certainty and omalizumab with moderate certainty; however, none reached the minimal important difference (MID). Both benralizumab and omalizumab improved QoL with high certainty, but only omalizumab reached the MID. Omalizumab enabled ICS dose reduction with high certainty. Benralizumab and omalizumab showed an increase in drug‐related adverse events (AEs) with low to moderate certainty. All three biologicals had moderate certainty for an ICER/QALY value above the willingness to pay threshold. There was high certainty that in children 6‐12 years old omalizumab decreased the annualized exacerbation rate [IRR 0.57 (95%CI 0.45‐0.72)], improved QoL [relative risk 1.43 (95%CI 1.12 −1.83)], reduced ICS [mean difference (MD) −0.45 (95% CI −0.58 to −0.32)] and rescue medication use [ MD −0.41 (95%CI −0.66 to −0.15)].